A ruptured bronchial artery aneurysm with massive haemoptysis - Ueda, Ryoma (BMJ Case Rep, 2017)
Massive haemoptysis is associated with high mortality. Among various diseases presenting with massive haemoptysis, a ruptured bronchial artery aneurysm (BAA) is a rare entity. We report the case of a ruptured BAA as small as 3 mm in diameter associated with massive haemoptysis in a previously healthy 77-year-old woman. She had suddenly developed massive haemoptysis and was intubated and admitted to the intensive care unit. A CT scan and repeated bronchoscopy could not reveal the cause. Because haemorrhage continued, she underwent bronchial arteriography (BAG) twice. We finally detected a BAA with a bleb that led to the diagnosis of a ruptured BAA only 3 mm in diameter. After bronchial artery embolisation, the haemoptysis ceased. Although rare, a ruptured BAA should be considered as a cause of massive haemoptysis. Because a small BAA may get overlooked, close observation is important in BAG.